Effect of Gooseberry Powder on the Shelf Life of Spent Hen Meat Pickle at Room Temperature : 10.5958/2581-6616.2020.00013.4 - Kumaresan, S.; Pal, U.K.; Kasthuri, S.; Mandal , P.K. (Journal of Meat Science, 2020)
Meat is a nutrient dense food. In view of worldwide demand for natural food additives, search for natural preservatives have notably increased for the ready-to-eat products in recent years. Hence, the present study was envisaged to assess the changes in quality of spent hen meat pickle (SHMP) prepared by using gooseberry powder (GBP) as natural preservative along with acetic acid during storage at room temperature. The products viz. SHMP containing 1% acetic acid (control), SHMPs with 2% GBP (T-1) and 3% GBP (T-2) along with 0.5% acetic acid were prepared and packed in PET (Polyethylene terephthalate) bottles. The products were stored at room temperature for a period of 60 days after a maturation period of 7 days. The control and treated products were evaluated for physico-chemical, sensory and microbiological quality at 10 days interval on 0, 10, 20, 30, 40, 50 and 60 days of storage. Significant differences (P<0.05) in proximate composition (moisture, protein and fat %) and pH between products and between storage days were observed. The protein and fat contents were significantly (P<0.05) higher for T-2 product than other products. T-2 product and the control sample showed lower pH values throughout the storage period than T 1 product. T-2 product had significantly (P<0.05) lower TBA values than control and T-1 products. There was gradual but significant (P<0.05) increase in TBA and tyrosine values in all the products with the advancement of storage period but values were much below the threshold of spoilage. The standard plate count (SPC) values were much below the permissible limit for all the products. All the products had very good sensory scores (>7 in 8 point hedonic scale) for all the sensory attributes throughout the storage period.